Pulse Wave Imaging (PWI) and arterial stiffness measurement of the human carotid artery: An in vivo feasibility study - Ronny X. Li (2018)
Noninvasive quantification of regional arterial stiffness has been shown to be of high clinical importance. Pulse Wave Imaging (PWI) has been previously developed by our group to visualize the propagation of the pulse wave along the artery and to estimate the regional pulse wave velocity (PWV). The objectives of this paper are to 1) determine the feasibility of PWI in the human carotid artery in vivo and 2) assess the stiffness of the human carotid artery in vivo using applanation tonometry and ultrasound-based motion estimation. For PWI, the left common carotid arteries of eight healthy volunteers were scanned with a 10 MHz linear array transducer at a high frame rate of 1127 Hz. The RF signals were used to estimate the axial velocity of the arterial wall using a 1D cross-correlation based speckle tracking method. Regional PWV was estimated from the spatiotemporal variation of the axial wall velocities and was found equal to 4.5 ± 0.4 m/s in eight subjects, in agreement with findings reported in the literature. PWI was thus proven feasible in the human carotid artery. For stiffness identification, the pressure and regional wall displacement of the carotid artery in seven healthy subjects were estimated. The circumferential stress-strain relationship was then established assuming (i) a linear elastic two-parallel spring model and (ii) a two-dimensional, nonlinear, hyperelastic model. A slope change in the stress-strain curve was defined as a transition point. The average Young's moduli of the elastic lamellae, elastin-collagen fibers, and collagen fibers were found to be equal to 0.15 ± 0.04, 0.89 ± 0.27 and 0.75 ± 0.29 MPa, respectively. The average incremental Young's moduli before and after the transition point of the intact wall were found to be equal to 0.16 ± 0.04 MPa and 0.90 ± 0.25 MPa, respectively. The before and after transition point moduli of the tunica adventitia were found to be equal to 0.18 ± 0.05 MPa and 0.84 ± 0.22 MPa, respectively. The before and after transition point moduli of the tunica media were found to be equal to 0.19 ± 0.05 MPa and 0.90 ± 0.25 MPa, respectively. Thus, the feasibility of measuring the regional stress-strain relationship and stiffness of the normal human carotid artery in vivo noninvasively was demonstrated. © 2011 IEEE.